THE EFFECT OF BRAND IMAGE AND PROMOTION OF WINGSCARE PRODUCTS ON BUYING DECISIONS IN EAST CIREBON WITH PURCHASE INTENTION AS THE INTERVENING VARIABLE - Iman Ahdiman; Adi Setiawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of brand image and promotion on the buying decision of Wings Care products in East Cirebon, with purchase intention as the intervening variable. The study uses a quantitative approach with a survey method involving 109 Wings Care consumer respondents. Data were collected using a five-point Likert scale questionnaire and analyzed using multiple linear regression with validity, reliability, and classical assumption tests. The results show that brand image and purchase intention have a positive and significant effect on buying decisions, while promotion has no significant effect. Purchase intention is the most dominant variable in driving purchasing decisions. Simultaneously, all independent variables have a significant effect on purchasing decisions, thus validating the model. These findings indicate that consumers, especially millennials, are more influenced by brand image and quality perception than by short-term promotions.